FROM LINGUISTIC CENTER TO ACADEMIC WRITING CENTER - Irina B. Korotkina (Высшее образование в России)
The author describes the experience accumulated by the Interdisciplinary Department of English, MSSES, in creating the innovative Western-type academic environment and its further development into an academic center focused on academic writing. She analyses the ways in which the Western model of academic writing could be applied to the Russian learning environment, and offers a concept of creating academic writing centers in Russian universities.